Nutritional quality of different starches in feed fed to juvenile yellow perch, Perca flavescens. (1st December 2019) - Jiang, Ming; Zhao, Huihong; Zhai, Shao‐Wei; Newton, Ryan J.; Shepherd, Brian; Tian, Juan; Lofald, Annamarie G.; Teh, Swee; Binkowski, Fred P.; Deng, Dong‐Fang
Abstract: This study determined whether accumulated liver and visceral lipid in yellow perch can be alleviated by feeding an appropriate starch source. We compared the growth performance, nutritional composition and health of yellow perch fed a control diet (no added starch) and three diets with corn, potato or wheat starch (200 g/kg diet) to replace an equal proportion of fishmeal in the control diet. Dietary starch led to increased bulk density, hardness and gelatinization levels of feed pellets compared with the control diet. At the end of an 8‐week feeding, all fish fed the test diets had similar growth rates ( p  > .05). However, the wheat starch diet resulted in significantly enlarged livers and increased accumulation of lipid in the liver, viscera and whole body ( p  < .05). This diet also caused significantly higher levels of fasting glucose, aspartate aminotransferase and alkaline phosphatase activities in serum than the control diet. Liver cell diameters were larger, and Kupffer cell numbers were lower in the fish fed the wheat starch than those fed the control diet. Potato or corn starch had less impact on fish health and is considered to be an appropriate carbohydrate sources for yellow perch under the current testing conditions.